Investigating the Underlying Mechanisms of Circular RNAs and Their Application in Clinical Research of Cervical Cancer - Liu, Jian; Zhu, He; Fu, Li; Xu, Tianmin (Frontiers in Genetics, 2021)
Circular RNAs (circRNAs) are non-coding RNA molecules, and these are differentially expressed in various diseases, including cancer, suggesting that circRNAs can regulate certain diseases. CircRNAs can act as miRNAs sponges, RNA-binding protein (RBP) sponges, and translation regulators, and they can become an important part of the regulation of gene expression. Furthermore, because of their biomedical features in body fluids, such as high abundance, conservation, and stability, circRNAs are seen as potential biomarkers for various cancers. Cervical cancer (CC) is one of the main causes of cancer-related death in women, and there have been a large number of studies that analyze circRNAs as a new object to be evaluated in CC. Therefore, this review, by understanding the role of circRNAs in CC, may create innovative strategies in the future clinical diagnosis, treatment, and prognosis of CC and promote the development of personalized and highly accurate cancer therapy.